PENDAMPINGAN PENINGKATAN NILAI TAMBAH LELE BAGI PEMBUDIDAYA DI DESA SOBIH KABUPATEN BANGKALAN - Aisya, Siti; Maulana, Eri; Destiarni, Resti Prastika (Politeknik Negeri Sriwijaya, 2024)
Sobih is one of 12 villages in Burneh District, Bangkalan Regency. The village's physical condition is fantastic, it is not polluted, and vacant land has not been used as a building. Some residents use this to cultivate catfish. Then, they formed the Super Madura Catfish Cultivator Group. This group produces catfish rearing, brooders, breeding, and catfish feed. Catfish are sold in fresh catfish and catfish seeds. Based on the interviews with group leaders, they want to develop processed catfish products to add value to the catfish of sale. They provide a solution for processed products in catfish dumplings based on existing potential. This program aims to introduce how to make catfish dumplings, which will increase the selling value of catfish through counseling, training, and mentoring. In this program implementation, several stages were carried out, namely, the planning stage, including surveys to target partners; the preparation stage, covering licensing, procurement of tools and materials, and schedule planning; then the implementation stage, covering socialization, training continued with application with assistance during direct practice by partners. Through this program, the group hoped to develop the production of processed catfish dumplings and increase the selling value of catfish and the group's income.